Controlled direction of electrical and mechanical properties in nickel tethered graphene polyimide nanocomposites using magnetic field. (April 2015) - Yoonessi, Mitra; Gaier, James R.; Peck, John A.; Meador, Michael A.
Abstract: Oriented hybrid nickel tethered graphene polyimide resin nanocomposites with different degrees of orientation were prepared by in-situ magnetic field solvent casting method. Magnetization of the hybrid Ni-graphene polyimide nanocomposites exhibited a maximum in the magnetic field direction and a minimum perpendicular to the magnetic field direction indicating the orientation of the superparamagnetic nickel nanoparticles. In-plane dc electrical conductivity of the 1.3 vol.% Ni-graphene was 2.5 times higher when cast in a high magnetic field compared to films cast without an applied magnetic field. The through-plane dc conductivity of the 1.3 vol.% oriented Ni-graphene polyimide nanocomposites decreased with increasing magnetic field strength and reached insulation (10 −12  S/cm) for the films cast in high magnetic field. The in-plane tensile modulus of the polyimide exhibited a 35% increase when 0.16 vol.% Ni-graphene was added to the polyimide and cast in a low-strength magnetic field. Further addition of Ni-graphene, up to 1.3 vol.%, to the polyimide resulted in nearly constant tensile moduli. Tensile strength of nickel graphene nanocomposites showed up to 2-fold increase compared to the neat polyimide. Scanning electron microscopy (SEM) revealed that the Ni-graphene nanosheets were oriented in the magnetic field direction.